PERANCANGAN TRANSPORTASI UMUM SHUTTLE BUS RAMAH LINGKUNGAN: Studi Kasus Daerah Jakarta Selatan - Marpaung, Jhon Viter; Tabrani, Wahyu Albin (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2018)
In recent years, innovative public transportation is developing in Indonesia, especially in big cities. This service consists of flexible transport services that can be ordered through online applications to well-designed buses. It is true that the average urban community chooses to use public transport services, but there are still certain kinds of communities such as upper-class people who prefer to use their private vehicles because they feel less flexible and comfortable when using public buses. This medium-sized hybrid bus intercity bus (shuttle bus) concept can help create better environmental quality for urban communities.